UPAYA PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN BAROKAH NANDAN SUKOHARJO MELALUI PROGRAM 3 SUKSES (Alim Faqih, Berakhlakul Karimah Dan Mandiri) - Alfauzi, Alfian; Choiriyah, Siti (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Pondok Pesantren Barokah Nandan Sukoharjo there are students who have knowledge but are not processed in daily life. Some of them lack the awareness of karimah in daily life. In anticipation of this, Pondok Pesantren Barokah Nandan Sukoharjo has a special program in shaping the character of its students, namely through the 3 Sukses program. The 3 successful program consists of Alim Faqih, Berakhlakul Karimah and Mandiri. In shaping the character of the students, program 3 successfully has a variety of activities that support in the formation of santri characters. So the researchers aim to know the implementation of program 3 success in shaping the character of the students. This research is a qualitative descriptive study. The research was conducted at Pondok Pesantren Barokah Nandan Sukoharjo in September 2018 until January 2019. The subjects in this study are Students, Students and Ustadz Pondok Pesantren. Data collection is conducted with observations, interviews and documentation. To find out the validity of the data use triangulation methods and triangulation of sources. Data is analyzed using interactive data analysis with data collection measures, data reduction, data presentation and conclusion. The results of the study concluded that the implementation of the 3 Sukses program was carried out by inviting students to participate in the activities in the 3 Sukses program (Alim Faqih, Berakhlakul Karimah and Mandiri). In Alim Faqih cluster, activities include: promo tinging the Qur'an and Al-hadith, fasting Monday-Thursday, praying 5 times, Tahajud, Dhuha. While on the cluster Berakhlakul Karimah his activities include: apple coaching morals, virtuous movement, hair style inspection, movement of wearing his own sandals. As well as self-contained clusters, activities include: charity movements, goats, catfish, washing their own clothes, selling ice and meatballs, cooking, and Persinas Asad